Pengaruh Repetitive Learning Method melalui Buku Cerita Bergambar terhadap Kemampuan Bicara pada Anak Autis - Anggraeni, Elok; Yaum, Lailil Aflahkul; Sukmawati, Bhennita (JOEAI (Journal of Education and Instruction), 2025)
This study aims to analyze the effect of implementing the Repetitive Learning Method (RLM) through storybook media on the speaking ability of Autistic children at SDI Achmad Jogoyudan Lumajang. The method used is Single Subject Research (SSR) with an A-B design, which consists of a baseline phase (A1) and an intervention phase (B1). The study's results showed a significant and stable increase. In the baseline phase (sessions 1-5), the subject's ability ranged from 24% to 36%. After the RLM intervention through storybooks, the subject's ability increased drastically and consistently, reaching 80% in the last session. Visual analysis between conditions (A1-B1) revealed a change in level of +8 points, indicating a positive trend, and an overlap percentage of 0%, suggesting that the Repetitive Learning Method (RLM) has a positive effect on improving speaking ability in Autistic children following the intervention. These findings confirm that the integration of RLM, with repetition priming and spaced repetition mechanisms, and engaging storybook media, synergistically creates an optimal learning environment to overcome verbal communication barriers in children with autism. The conclusion is that the implementation of the Repetitive Learning Method (RLM) through storybooks has an impact on the speech skills of autistic children at SDI Achmad Jogoyudan Lumajang.   Keywords: Autistic Children, Storybooks, Verbal Communication, Repetitive Learning Method